Blended Learning - Shahzoda Umarova Iqboljon qizi (Zien Journals, 2024)
Despite the fact that its effectiveness promotes more learners to be engaged, developing world faces challenges to make it more innovative in the process of teaching. It leads to some questions about whether or not this new approach is effective, what are the results in terms of learning outcomes, what difficulties can emerge and how they can be overcome. This paper examines these questions and discusses possible answers: increased student engagement and achievement, improved satisfaction and effectiveness are two different positive outcomes of blended learning approach for students whereas technological and learning environment challenges can be dealt with two varied ways: utilization of Learning Management System (LMS) and teachers’ competence to apply different techniques during the sessions.
Keywords: Blended learning; Learning Management System; online and offline mode of learning